Profitability's Ability to Moderate the Effect of Carbon Emission Disclosure and Environmental Performance on Firm Value - Purnama Sari, Siti Nuralisya; Paramita, Veronika Santi (Moneta : Journal of Economics and Finance, 2025)
This study aims to examine the effect of carbon emission disclosure (CED) and environmental performance on firm value, with profitability acting as a moderating variable. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. A quantitative approach using descriptive-causal analysis was applied. The study used secondary panel data obtained from financial and sustainability reports. Thirteen energy companies were selected through purposive sampling. Data were analyzed using panel data regression and moderated regression analysis (MRA). The results show that CED does not significantly affect firm value, while environmental performance has a positive impact. Profitability does not moderate the relationship between CED and firm value but does strengthen the influence of environmental performance on firm value. These findings highlight the importance of environmental initiatives combined with strong financial performance in enhancing firm value. For corporate managers and policymakers, this underscores the need to integrate sustainability practices into strategic decision-making to improve long-term firm valuation.